2017
DOI: 10.4317/jced.53652
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of impacted upper canines: Panoramic radiograph Vs Cone Beam Computed Tomography

Abstract: BackgroundThe use of CBCT exam in the study of IMC is not new. However, it’s still not known in what specific aspects CBCT exam shows a better result than then conventional exams. The aim of this study was to compare and conclude in what way the opinion regarding upper canine impaction differed when observing a panoramic image compared to the observation of a set of CBCT reconstructions.Material and MethodsTwenty patients (10 males and 10 females) with a total of 28 impacted maxillary canines were identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
0
24
0
4
Order By: Relevance
“…Additionally, Queck et al 2003 suggested that the gender differences may be caused by the fact that the skull and jaw sizes are smaller in women than in men and a proper jaw size is an important factor that helps the development and eruption of teeth in exact order and place 24 . However, other studies as Pico et al 2017 found the number of male and female patients in a ratio of 1:1 and justified that by their reduced sample size (only 28 impacted canines in 20 patients) 25 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, Queck et al 2003 suggested that the gender differences may be caused by the fact that the skull and jaw sizes are smaller in women than in men and a proper jaw size is an important factor that helps the development and eruption of teeth in exact order and place 24 . However, other studies as Pico et al 2017 found the number of male and female patients in a ratio of 1:1 and justified that by their reduced sample size (only 28 impacted canines in 20 patients) 25 .…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, 75% of maxillary impacted canine cases were unilateral while only 25% were found bilaterally. Similarly, Pico et al 2017 found that the frequency of unilateral and bilateral impactions was 60% and 40% respectively 25 . Moreover, another previous study showed that the majority of impactions of maxillary canines are unilateral at 92%, and only 8% are bilateral 27 .…”
Section: Discussionmentioning
confidence: 91%
“…It has shown varying insights and conclusions. Pico et al [ 42 ] stated in 2017 that further research is necessary to prove when CBCT has a clear advantage over conventional 2D radiographs. In 2019, Björksved et al [ 43 ] concluded that “panoramic radiographs could be considered good enough for rendering palatally displaced canine position when the need for 3D information is not crucial for treatment planning”.…”
Section: Limitations Of the Guideline And Recommendations For Future mentioning
confidence: 99%
“…In previous studies, the authors compared CBCT and OPG on many different aspects such as: surgical technique of maxillary and mandibular third molar, classifying of lower third molar, upper molar root protrusion into maxillary sinus, relation of impacted mandibular third molars to the inferior alveolar nerve, presurgical evaluation of bony implant sites, impacted maxillary canines, and anatomical characteristics and visibility of mental foramen and accessory mental foramen (Ghaeminia et al,2009;Aravindaksha et al, 2015;Lorenzo et al, 2015;Pico et al, ;Araujo et al, 2019;Hermann et al, 2019;Brasil et al, 2019;Themkumkwun et al, 2019;Nirmalendu et al, 2019;Fortes et al, 2019). None of the prior studies compared CBCT and OPG films taken after the marsupialization of odontogenic cysts in terms of evaluating whether the odontogenic cyst volume allows enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…According to their results 83.87% of the mental foramens and 45.83% of the accessory mental foramens identified on CBCT were also visible on panoramic images. A questionnaire implemented by Pico et al (2017) reported that the CBCT imaging gave further information when compared to panoramic radiography regarding the impacted upper canine assessment. This questionnaire was performed with nine orthodontists and they were asked to analyze different topics regarding the impacted maxillary canines.…”
Section: Discussionmentioning
confidence: 99%